Determinants of nutritional status among old age population in eastern Ethiopia: a general linear model approach. (26th August 2022) - Derbie, Liyu; Oumer, Abdu; Ayele, Ketema; Berhane, Anteneh
Abstract: As the world's aging population grows, nutrition and health issues are becoming a major concern. The aim of the present study was to identify the factors associated with nutritional status among old age population. A community-based cross-sectional study was employed among randomly selected 739 elders over the age of 60 in Dire Dawa City administration, eastern Ethiopia. The validated full mini nutritional assessment tool and appetite test (SNAQ) was used to assess the nutritional status of the study population. Considering the ranked nature of the data, a bivariate and multivariable ordinal logistic regression model (under the generalised linear model) was conducted, with crude and adjusted odds ratios reported along with 95 % confidence intervals. Statistically significant associations are declared at P -value less than 0⋅05. In this study, 22 % (95 % CI: 19 %, 25 %) of elders were malnourished. Participants with >75 years old (AOR 4⋅95; 95 % CI 1⋅54, 8⋅4), being female (AOR 1⋅6; 95 % CI 1⋅1, 2⋅2), illiterate (AOR 1⋅5; 95 % CI 1⋅01, 2⋅2), severe depression (AOR 13⋅9; 95 % CI 8⋅2, 23⋅7) and with poor appetite (AOR 3⋅3; 95 % CI 2⋅3, 4⋅8) were important predictors of malnutrition among older age group. We found that the prevalence of malnutrition and the risk of malnutrition is a public health concern that warrants intervention in the area. Advanced age, illiteracy, depression and poor appetite were important risk factors for malnutrition among older age group. The identified risk factors will guide public health professionals and programmes in the design, implementation of interventions to improve the nutritional status of older age group.